Female labour force : impact of the childcare factor - Chua, Siew Chin (2014)
Manpower policy is a central concern of the government. As labour shortage and escalating costs threaten to erode Singapore's competitiveness, there is an urgency to mobilise the inactive potential sources, especially the married women. Coupled with this is the growing concern that the persistence of delayed child-bearing and smaller families may create social and demographic problems.